ANALISIS ENERGI PENGERINGAN PADI MENGGUNAKAN VERTICAL DRYER TYPE VRD60 DI DESA BIGO SELATAN KABUPATEN BOLAANG MONGONDOW UTARA - Lengkey, Giovanni (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2020)
The purpose of this study is calculating the total energy needed during the rice drying process by using a vertical dryer VRD60 type in Bigo Selatan Village, Kaidipang Subdistrict, North Bolaang Mongondow District, and determining the efficiency of energy use during the rice drying process. The tools used were: AGRINDO dryer VRD60 type, Danoplus infrared thermometer THE-223, Sima brand weighing scale with the capacity of 500 kg, and CROWN digital grain moisture meter. Materials used were: 5,202 kg (5.2 tons) of Sultan rice variety, diesel fuel, and rice husks. The study was conducted with experimental and survey methods. Data was analyzed descriptively. The results showed that the total energy used by the dryer is 1,531,560 kcal consist of 6,300 kcal labor (humans) energy, 683,760 kcal of diesel fuel and 841,500 kcal of energy from husk usage. The biggest energy is obtained from the husk used as much as 255 kg with a calorific value of 841,500 kcal and the biggest use is to evaporate water from materials that is 450,293.1 kcal. The energy efficiency of drying from a vertical dryer VRD60 type is found to be 38.29%.